2020
DOI: 10.1080/13506285.2020.1764156
|View full text |Cite
|
Sign up to set email alerts
|

Memory for action: a functional view of selection in visual working memory

Abstract: Perception is shaped by actions, which determine the allocation of selective attention across the visual field. Here, we review evidence that maintenance in visual working memory is similarly influenced by actions (eye or hand movements), planned and executed well after encoding: Representations that are relevant for an upcoming actionbecause they spatially correspond to the action goal or because they are defined along action-related feature dimensionsare automatically prioritised over action-irrelevant repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 121 publications
5
73
0
1
Order By: Relevance
“…Our results build on and extend several lines of prior research that have linked visual working memory and action (23)(24)(25). For example, it has been established that overt actions can themselves influence visual working memory performance (24,44,45) and that brain structures that control action also participate in visual working memory (46,47).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results build on and extend several lines of prior research that have linked visual working memory and action (23)(24)(25). For example, it has been established that overt actions can themselves influence visual working memory performance (24,44,45) and that brain structures that control action also participate in visual working memory (46,47).…”
Section: Discussionsupporting
confidence: 85%
“…Our results build on and extend several lines of prior research that have linked visual working memory and action (23)(24)(25). For example, it has been established that overt actions can themselves influence visual working memory performance (24,44,45) and that brain structures that control action also participate in visual working memory (46,47). We investigated the complementary direction of this interaction, revealing that the selection of visual information into working memory also naturally recruits the preparation for prospective manual actions [see also (19)(20)(21)(22)].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Extending this to the domain of working memory, recent studies have shown that goal-directed eye movements made after visual encoding can still facilitate performance of spatially-congruent items (here, congruent with memorized item location) (Hanning & Deubel, 2018 ; Hanning et al, 2016 ; Ohl & Rolfs, 2017 , 2018 ); see also (Bays & Husain, 2008 ). This work is also reviewed in more detail in a complementary article by Heuer et al ( 2020 ) in this special issue. This has been shown to occur so automatically that congruent-item benefits persist even when the saccade-congruent item is less likely to be probed for report after the memory delay (Ohl & Rolfs, 2017 , 2020 ).…”
Section: Involuntary Influencesmentioning
confidence: 99%
“…In addition to attentional prioritization at the level of memory items, it has recently become clear that feature-dimensions – that are shared across memory items – can also be prioritized in visual working memory (Hajonides et al, 2019 ; Niklaus et al, 2017 ; Park et al, 2017 ; Pilling & Barrett, 2016 ; Ye et al, 2016 ). Such feature-dimension prioritization has been reported to be contingent on actions as well; such that plans for distinct types of manual actions (grasp vs point) facilitate distinct feature-dimensions of visual information in memory (size vs colour) (Heuer & Schubö, 2017 ); see also (Heuer et al, 2020 ).…”
Section: Involuntary Influencesmentioning
confidence: 99%